EP222 Indocyanine green for sentinel lymph node detection in early breast cancer: prospective evaluation of detection rate and toxicity. (1st November 2019) - Ngô, C; Sharifzadehgan, S; Lecurieux-Lafayette, C; Belhouari, H; Rousseau, D; Bonsang-Kitzis, H; Crouillebois, L; Oudard, S; Lécuru, F; Elaidi, R-T
Abstract : Introduction/Background: Detection of sentinel lymph node (SLN) in early breast cancer is commonly based on the combination of patent blue dye and a radio isotope (RI) 99m Technetium. Each of these two tracers has advantages and disadvantages leading to the development of the use of Indocyanine Green (ICG) as a new tracer. Methodology: We conducted a prospective clinical trial to evaluate the detection rate of ICG, the sensitivity and concordance rate as compared to 99mTe. Each patient undergoing a SLN biopsy for an early breast cancer received both ICG and RI. The trial was registered: FLUOBREAST EudraCT N°2015-000698-11, ClinicalTrials.gov Identifier: NCT02875626 . Results: Seventy-seven patients were analysed with a total of 205 nodes. Detection rates were 93% for the RI and 96% for the ICG. Combined detection rate was 99%. Sensitivity of the ICG was 100%. Overall concordance rate was 91%. Median numbers of excised SLN was 2.3 for both tracers and 2.7 for the combined method (p=0.21). All the macrometastatic nodes were detected by the ICG. Median time between skin incision of the axilla and removal of the last SLN was 14 min. There was no allergy to the ICG. There was no radio-sensitization linked with the use of ICG. Conclusion: ICG allows high detection rate and high sensitivity for the SLN biopsy in early breast cancer, with short operative time and a usual number of excised SLN. Allergy is extremely rare and there is no toxicity. ICG could be an alternative to RI to provide an accurate staging of the axilla. Its routine use should be approved for SLN biopsy. Disclosure: Nothing to disclose.